Análisis cualitativos de metodologías de mejora continua para la generación de una herramienta guía aplicable al sector de lácteos. Caso de estudio : Pymes Mexicanas y Colombianas. (2017)
The objective of the research is to develop a qualitative analysis to understand the main advantages and disadvantages that avoid small and medium enterprises (SMEs) in the dairy sector of Latin America and the Caribbean (LAC) from developing their work processes based on continuous improvement tools. In addition, to develop a guide tool that allow them to manage their processes in a clear and simple manner. 758 SMEs of the dairy sector in 10 LAC countries are analyzed, identifying their main limitations and virtues in their work processes. The same points are analyzed in 1,950 SMEs in the sector in 10 countries of the European Union (EU) and others in the world, in order to make a qualitative comparison of the main differences and similarities of the advantages and disadvantages in the adoption of continuous improvement work techniques. Subsequently, a semi-structured interview was designed and applied for 6 dairy SMEs in Veracruz, Mexico and 6 dairy SMEs in Bogotá, Colombia. Highlighting results such as deficiencies in the structure and organizational development, production planning, relationship with suppliers and customers. Therefore, the design of the guide tool is fundamental since it integrates continuous improvement techniques that allow dairy SMEs to manage and control their processes in a clear and simple manner, combining a series of indicators that help them evaluate their performance.